2019
DOI: 10.1002/rra.3506
|View full text |Cite
|
Sign up to set email alerts
|

A seasonal forecasting procedure for reservoir inflows in Central Asia

Abstract: This study develops a procedure for seasonal forecasting river discharge from headwaters above strategically important hydropower plants in Kyrgyzstan and Tajikistan. The El Niño Southern Oscillation, North Atlantic Oscillation, and Indian Ocean Dipole indices were used as inputs. Predictability was evaluated for average summer inflows conditional on the tercile of the preceding winter climate mode. We find that the winter Niño 3.4 index was significantly positively correlated with following summer inflows to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 49 publications
1
5
1
Order By: Relevance
“…This is consistent with earlier findings (e.g. Mariotti 2007, Wang et al 2014, Dixon and Wilby 2019, Gerlitz et al 2019, albeit our spatial scales are different and the targeted seasons do not precisely align.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is consistent with earlier findings (e.g. Mariotti 2007, Wang et al 2014, Dixon and Wilby 2019, Gerlitz et al 2019, albeit our spatial scales are different and the targeted seasons do not precisely align.…”
Section: Discussionsupporting
confidence: 92%
“…Knowledge about the impacts of the Indian Ocean Dipole (DMI), an irregular oscillation of sea surface temperature between the western and eastern parts of the Indian ocean (Saji et al 1999), is patchy. Existing evidence suggests that summer runoff fluctuations in main tributaries of the Amu-Darya, the largest river in the region which originates in the Pamir mountains, are negatively associated with DMI (Dixon and Wilby 2019). However, the timing of this relationship remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Different literature work reviews across the globe have found a nonlinear or linear relationship between station elevation and rainfall pattern, e.g., the Kruger National Park, South Africa and Mount Kenya, East Africa (Hawinkel et al 2016;MacFadyen et al 2018). Likewise, a linear pattern was found in a Spatio-temporal Island study in a European City (Arnds et al 2017;Sohrabi et al 2017) while a nonlinear relation exists in a central Asia Basin study (Dixon and Wilby 2019).…”
Section: Introduction Backgroundmentioning
confidence: 94%
“…McGregor () contributes to theme 2 (river flows and flow regimes) by considering the links between climate and rivers, emphasising linkages with flow regimes and hydrological variability and introducing the concept of atmospheric rivers. Dixon and Wilby () further develop atmosphere—river flow linkages by illustrating how seasonal inflows to rivers feeding strategically important hydropower plants in Kyrgyzstan and Tajikistan can be forecast using information on El Niño conditions. Nestler, Milhous, Payne, and Smith () focus on hydraulic conditions within rivers, providing the multi‐decade history and a review of the Habitat Suitability Criteria Curve as a tool to address water resource issues.…”
Section: Special Issue Papersmentioning
confidence: 99%